HUBUNGAN TINGKAT KEPATUHAN MINUM OBAT DENGAN PERUBAHAN KADAR CD4 PADA PASIEN HIV/AIDS DI POLI VCT RSUD Prof. Dr. SOEKANDAR MOJOSARI MOJOKERTO - Windartik, Emyk; Sajidin, M. (JURNAL KEPERAWATAN BINA SEHAT, 2015)
HIV is a disease that has not found a cure. Virus in the patients body can not get out, so one must consume a lifetime of antiretroviral drugs and timely. Schedule of taking HIV medication is not to be missed in order to suppress the sheer number of viruses in the body. If not disciplined then the drug will become resistant to the body and cause a decrease in CD4 levels and macrophages. The design used this study is descriptive. Its population is around the status of medical records of patients with HIV / AIDS status of data as much as 53 patients undergoing treatment at the Poly VCT taken by total sampling technique to obtain the status of a data sample of 53 patients. In this study, the independent variable is the level of medication adherence in HIV / AIDS, the dependent variable is the change of CD4 HIV / AIDS patient. Data collected using observation sheet. Once the data is collected and analyzed the data by using cross tabulation. The results showed an association level of adherence to the changing levels of CD4 in HIV / AIDS. Compliance is a very important factor in the treatment. If the patient is not adherent indirectly can be identified by changes in the patients own CD4 levels. The role of the PMO greatly affect patients taking medication schedule. Therefore, taking medication supervision by the PMO is expected to be further enhanced to be able to increase levels of CD4 and general condition of the patientKeywords:Compliance,Changes ofCD4, HIV/AIDS